KINERJA KOMISI PEMILIHAN UMUM DAERAH KABUPATEN SUKOHARJO DALAM PENYELENGGARAAN PEMILIHAN LEGISLATIF TAHUN 2014 DI KABUPATEN SUKOHARJO - Damayanti Suhita, Anna Aprilia S, Aris Tri Haryanto & (Transformasi, 2016)
The purpose of this research was to find out the performance of KPU in Sukoharjo regency inorganizing legislative elections in year of 2014. This research use descriptive-qualitativemethod. The research of informant use purposive sampling. Then the data source use primaryand secondary data. The data collection technique use interview and documentation. In thisresearch also using interactive analysis technique. The results of this research are: (1) Inorganizing the legislative election in year of 2014, the performance of KPU of Sukoharjo wasgood enough. We could see that they did the all of the legislative election process in compliancewith the schedule, and also based of their vision and mission. (2) From the human resourceaspect, KPU of Sukoharjo regency has enough member and committee of organizing the electionwhich as Ad Hoc, they have 15.017 people of human resources. They also have the goodinfrastructure. (3) If from estimate aspect, the cost estimate that they got was from APBN. In itsexecution, KPU of Sukoharjo was efficient and effective enough. (4) KPU in collaboration withCounty Police (polres) and District Military Command (Kodim) until stage of KPPS together didthe distribution of the logistics. They used about 7 trucks to carry the logistics. (5) The conceptwhich was did of Sukoharjo’s KPU in increasing the people participation was by electronicmedia that was radio, then face to face communication with the people, until did the activity ormassal event. (6) The performance of KPU of Sukoharjo regency of their effort to increase thepolitic participation of the people in legislative elections in year of 2014 got a number ofpercentages as much as 75.42%.Key Words: Performance, KPU of Sukoharjo Regency, Legislative elections.